Survey of viral reactivations in elite athletes: A case-control study - Pyöriä Lari; Valtonen Maarit; Luoto Raakel; Grönroos Wilma; Waris Matti; Heinonen Olli J.; Ruuskanen; Olli; Perdomo; Maria F. (MDPI, 2022)
Exercise-induced immune perturbations have been proposed to increase susceptibility to viral infections. We investigated the replication of persisting viruses as indicators of immune function in elite cross-country skiers after ten months of sustained high-performance exercise. The viruses evaluated, nine human herpesviruses (HHVs) and torque teno virus (TTV), are typically restrained in health but replicate actively in immunosuppressed individuals. We collected sera from 27 Finnish elite cross-country skiers at the end of the competition’s season and 27 matched controls who perform moderate exercise. We quantified all the HHVs and—TTV via highly sensitive qPCRs. To verify equal past exposures between the groups, we assessed the IgG antibody prevalences toward HHV-4 (Epstein–Barr virus, EBV) and HHV-5 (human cytomegalovirus, HCMV). We found equal TTV DNA prevalences in athletes (63%) and controls (63%) and loads with respective geometric means of 1.7 × 103 and 1.2 × 103 copies/mL of serum. Overall, the copy numbers were low and consistent with those of healthy individuals. Neither of the groups presented with herpesvirus viremia despite similar past exposures to HHVs (seroprevalences of EBV 70% vs. 78% and HCMV 52% vs. 44% in athletes and controls, respectively). We found no evidence of increased replication of persistent viruses in elite athletes, arguing against impaired viral immunity due to high-performance exercise.